Three Different Cherry Orchards, Three Different Worlds: Chekhov at the BBC, 1962–81. Issue 3 (November 2014) - Smart, Billy
Unlike the theatre, there is no established tradition of plays being revived (new productions made from existing scripts) on television. The only instance of this mode of production in Britain has been the regular adaptation of classic theatrical plays. The existence of three separate BBC versions of Chekhov's The Cherry Orchard (1962, 1971, 1981) creates a rare opportunity to trace developing styles of direction and performance in studio television drama through three different interpretations of the same scene. Through close analysis of The Cherry Orchard, I outline the aesthetic and technological development of television drama itself over twenty years.